Tinjuaan Pola Pengembangan Perpustakaan Politeknik Medica Farma Husada Mataram - Ikhwan Ikhwan (THE LIGHT : Journal of Librarianship and Information Science, 2023)
The existence of a university library is very important in an effort to improve the quality and human resources, both lecturers, employees and students, as well as the life and splendor of scientific activities in universities very much depends on the health of the existing library. The Medica Farma Husada Mataram Polytechnic Library as a means of supporting education, hopes to make a major contribution to the development and progress of the academic community. If seen from the graph of the development of the study program followed by the increase in the number of students, it must also be followed by changes and development of the library.The purpose of writing this article is to find out a review of the pattern of development of the Medica Farma Husada Mataram polytechnic library.The method used in this paper is a descriptive research model because descriptive research can be interpreted as a problem solving process that is investigated by describing the current state of the subject and object of research based on the facts that appear or as they are.The results of the study show that the Medica Farma Husada Mataram Polytechnic Library has good service performance which is guided by the existence of user services which have a philosophy of being more than just an effort to provide services when needed by the user (client-respondencess), more than that, they always try to provide guidance services by providing library materials. to be read by the user (client-focus). In general, procurement and collection development activities are still the same as those carried out by other universities that have been running so far. This activity does not involve many parties such as students, lecturers, employees, so that sometimes collections are not utilized by users. In accordance with the functions and duties of the library as a collector, manager, preservation and dissemination of information, the Medica Farma Husada Mataram Polytechnic Library has its own budget and policies in managing the library in accordance with the library organizational structure of the Medica Farma Husada Mataram Polytechnic library. Total Human Resources 3 (three) people, 2 people who have qualifications in the field of libraries. The Medica Farma Husada Mataram Polytechnic Library has not been directed to user oriented. This can be seen by the hours of service that are not adapted to the teaching and learning process, do not involve students in the selection and procurement of collections, and the available budget is not sufficient.The conclusion is that the pattern of developing the Medica Farma Husada Mataram Polytechnic library has been carried out quite well, this can be seen by the efforts made by librarians in service, namely service not only when students visit the library, but also at certain times and at certain times the librarian provides guidance to each student both in groups and during student orientation. The availability of the library's micro organizational structure management is also part of the library's development efforts in terms of library management and clarity of tasks and functions of the library at the Politeknik Medica Farma Hsuada Mataram. Library automation already exists, namely by using the Slim application so that it is easier and more effective in serving students. Human Resources already has a professional staff in the field of libraries.